A study on factors influencing students’ performance: a case study of UiTM Kedah / Norhidayah Ali …[et al.] - Ali, Norhidayah; Ali, Syukriah; Mokhtar, Najah; Andin Salamat, Azni Syafena (Research Management Institute, 2009)
Many studies are carried out to explore factors affecting students’ performance (academic achievement). The purpose of this research is to identify and examine factors that affect students’ performance at UiTM Kedah. A set of questionnaires was distributed to the respective respondents. Several factors that being discussed in this research are demographic, active learning, students’ attendance, involvement in extracurricular activities, peer influence and course assessment. The data is analysed using descriptive analysis, factor analysis, reliability testing and Pearson correlation of Statistical Package for Social Sciences (SPSS). After conducting factor analysis, all variables are grouped into five factors which exclude peer influence. We found that four factor are positively related to students’ performance that are demographic, active learning, students’ attendance and involvement in extracurricular activities. However, course assessment was found to be negatively related to students’ performance. Further research on students’ performance can be conducted on a larger scale including all UiTM to obtain better result.